2012
DOI: 10.1111/j.1748-5967.2012.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase trend of social hymenoptera (wasps and honeybees) in urban areas, inferred from moving‐out case by 119 rescue services in Seoul of South Korea

Abstract: The number of social hymenoptera have decreased due to accelerated urbanization in Seoul, Korea, during the 1970s–1990s. However, recent changes in environmental conditions have brought distinct re‐growth of their colonies. In this study, we analyzed the re‐colonization trend of social hymenoptera in Seoul with moving‐out reports submitted to 119 rescue services from 2000 to 2009. A total of 14 253 social hymenoptera findings and treatment cases were reported during that time, and the reported numbers increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In fact, V. velutina has become the most abundant Vespa species in Busan region (South Korea), displacing other species, such as V. simillima Smith (Choi et al, 2012a). Despite being introduced in Korea in 2003 (Kim et al, 2006), the overwhelming of other native vespids and subsequent predominance in urban areas suggest that V. velutina might be very adaptable to such enviroments (Choi et al, 2012b). There are several cases among Vespidae in which native species are affected by alien ones, as a consequence of interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, V. velutina has become the most abundant Vespa species in Busan region (South Korea), displacing other species, such as V. simillima Smith (Choi et al, 2012a). Despite being introduced in Korea in 2003 (Kim et al, 2006), the overwhelming of other native vespids and subsequent predominance in urban areas suggest that V. velutina might be very adaptable to such enviroments (Choi et al, 2012b). There are several cases among Vespidae in which native species are affected by alien ones, as a consequence of interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable that media coverage should be increased in the fall given that outdoor activities are frequent in the fall, which coincides with the frequency of reported injury and poisoning by warps (Choi et al . ). However, some media reports contained information relating to V. velutina that had not been scientifically proven.…”
Section: Discussionmentioning
confidence: 97%
“…This may reflect a general perception that urban wildlife is a nuisance [10]. Other studies have also suggested that urban residents are less tolerant toward wild animals than rural residents are, or that they switch to negative from positive when the animals cause problems [44, 45, 46]. Because the wildlife tolerance levels were measured for wildlife inhabiting nearby green spaces without any government intervention, the low tolerance levels indicate the high public dependency on government services to deal with wildlife problems.…”
Section: Discussionmentioning
confidence: 99%